Identifikasi Sifat Ketahanan Plasma Nutfah Kedelai (Glycine Max L. Merrill) Terhadap Kutu Kebul (Bemisia tabaci Genn.) - Reza, Nisrina Saraswati; Sulistyo, Apri; Purnamaningsih, Sri Lestari (Department of Agronomy, Faculty of Agriculture, Brawijaya University, 2019)
Superior variety with resistance to pest is neededin order to cover the high needs of soybean in Indonesia. Genetic resources from germplasm collections are needed for the assembly of new soybean variety resistant to whitefly. This research aims to find soybean germplasm as the source ofresistance gene and to learn soybean leaf characters resistant to whitefly. This research was conducted from February to May 2018 at Kendalpayak Experimental Station, Balitkabi, Malang. A total of 48 soybean genotypes were evaluated following a randomized block design with three replicates. Observations of whitefly population (number of eggs, nymphs, pupae, and imago), number of leaf trichomes, leaf chlorophyll index, leaf water content, and leaf color score were carried out on three plant samples for each genotype. The result showed that there are 6 resistant genotypes such as Wilis, Meratus, Argomulyo, Ringgit, Merbabu, and Malabar. There were no leaf characteristics that played a doimant role in soybean resistance to whitefly.